Data from the Human Penguin Project, a cross-national dataset testing social thermoregulation principles - Hu, Chuan Peng (2019)
Fundig agencies: Veni grant of the Netherlands Organization for Scientific Research (NWO) (grant nr. 016.145.049) and French National Research Agency "Investissements d'avenir" program (grant nr ANR-15-IDEX-02)